Persepsi Alumni Program Studi Komunikasi dan Penyiaran Islam dengan Stakeholder terhadap Kesesuaian Kurikulum dalam Dunia Kerja - Fita Fathurokmah; Masran Muin; Iin Ulfatul Hasanah (Dakwah: Jurnal Kajian Dakwah dan Kemasyarakatan, 2023)
The success of an institution that produces its graduates is seen from the extent to which graduates can practice knowledge in their fields in society. Therefore, to see to what extent graduates of the Islamic Communication and Broadcasting study program, Faculty of Dakwah and Communication Studies, UIN Syarif Hidayatullah Jakarta can benefit society, it is necessary to carry out tracking (Tracer Study). This alumni tracking seeks information regarding the whereabouts of graduates. It is difficult to know the number of graduates absorbed in the world of work. The suitability of graduates' work fields cannot be known, as well as the abilities of graduates from the point of view of users (stakeholders). Therefore, this research was conducted.               The main findings are the perceptions of alumni from the Islamic Communication and Broadcasting Study Program with Stakeholders regarding the suitability of the curriculum in the world of work that is not optimal according to the profile of graduates. A professional certificate is required for KPI Study Program graduates issued by UIN Syarif Hidayatullah Jakarta along with trade involving collaborations such as the Ministry of Manpower and the Ministry of Communication and Information. In fact, only graduates from the class of 2015 are the first to receive a diploma companion, which is called a Diploma Companion Certificate (SKPI).               Based on gender, it was found that the alumni of the Islamic Communication and Broadcasting Study Program (KPI) of the Faculty of Da'wah and Communication Sciences of UIN Syarif Hidayatullah Jakarta alumni from 2011 to 2015 received 59.47% for males and 67.53% for females. Respondents who have not worked amounted to 13 people or the equivalent of 13 percent, and those who have worked amounted to 113 people or the equivalent of 90 percent. The variations in the work of alumni of the Islamic Communication and Broadcasting Study Program, Faculty of Da'wah and Communication Sciences, UIN Syarif Hidayatullah Jakarta, Class of 2011 to 2015, consist of three major groups, namely working in private agencies, government agencies, and entrepreneurs or self-employed.